Garantia de qualidade em frigorífico de bovinos - Vieira, Kaio Venício dos Santos (Universidade Federal do Tocantins, 2022)
The present work reports the activities developed during the supervised curricular internship, the last subject taken to complete the Veterinary Medicine course, at the Federal University of Tocantins (UFT). It lasted 345 hours, from September 20th to November 22nd, 2021. The internship was developed in the Quality Assurance area, at the Masterboi slaughterhouse, in Nova Olinda - TO, under the supervision of the Zootechnician and Coordinator of the Quality Assurance Patrícia Rodrigues Teixeira and supervision of Prof. Dr. Francisca Elda Ferreira Dias. The internship activities were focused on quality control, aiming to guarantee the innocuousness, identity, integrity and quality of the products. All activities were carried out in conjunction with the establishment's Quality Assurance team. The report describes the main quality control tools and the production steps, from obtaining the raw material to shipping the products. The internship allowed them to experience practically the entire routine of a slaughterhouse, including the production and shipment of products to different places in Brazil and the world.